A representação do índio no cinema brasileiro: Yndio do Brasil (1995) de Sylvio Back e Terra Vermelha (2008) de Marco Bechis - Mello, Ana Lucia Annoni de (2015)
By analyzing two chosen films, this study aimed to discuss in what manner a cultural production contributes to address the social tensions caused by the growing presence and participation of indigenous communities in our days. The cinema creates versions of reality, selecting and developing inside the movies a particular meaning, made with our historical references. Both films expose the diversity of the imaginary developed among the society, representing indigenous communities, as well as the contradictions of the ideological discourse and state policies adopted throughout the Brazilian modernization process